2010
DOI: 10.1111/j.1365-2621.2010.02358.x
|View full text |Cite
|
Sign up to set email alerts
|

Original article: Supercritical CO2 extraction of soybean oil: process optimisation and triacylglycerol composition

Abstract: Supercritical CO 2 extraction of soybean oil was performed. Response surface methodology was applied to evaluate the effects of pressure, temperature and extraction time on soybean oil yield. The analysis of variance showed that pressure and extraction time followed by the quadratic term of pressure and interaction between pressure and time had the significant effect on the oil yield. The maximum extraction yield (6.59 ⁄ 100 g soybeans) at constant CO 2 flow rate of 1.629 L per min was achieved at 50°C, 300 ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 34 publications
(35 reference statements)
0
24
0
Order By: Relevance
“…The major TAGs were LLL (trilinolein), LLO (dilinoleoolein), LLP (dilinoleopalmitin), and LOP (linoleooleopalmitin). Jokić et al (2010) reported that in soybean oil obtained by supercritical CO 2 higher contents were obtained of triacylglycerols with unsaturated fatty acids (linoleic and linolenic acid), while the extraction with organic solvent resulted in increased contents of triacylglycerols with saturated fatty acids (palmitic and stearic acid). This is associated with the solubility of certain components in supercritical carbon dioxide, and can be explained by the fact that TAGs with higher unsaturation dissolve better in supercritical carbon dioxide than TAGs with lower unsaturation, or that the lighter TAGs are more soluble than the heavier ones (Davarnejad et al 2008).…”
Section: Resultsmentioning
confidence: 99%
“…The major TAGs were LLL (trilinolein), LLO (dilinoleoolein), LLP (dilinoleopalmitin), and LOP (linoleooleopalmitin). Jokić et al (2010) reported that in soybean oil obtained by supercritical CO 2 higher contents were obtained of triacylglycerols with unsaturated fatty acids (linoleic and linolenic acid), while the extraction with organic solvent resulted in increased contents of triacylglycerols with saturated fatty acids (palmitic and stearic acid). This is associated with the solubility of certain components in supercritical carbon dioxide, and can be explained by the fact that TAGs with higher unsaturation dissolve better in supercritical carbon dioxide than TAGs with lower unsaturation, or that the lighter TAGs are more soluble than the heavier ones (Davarnejad et al 2008).…”
Section: Resultsmentioning
confidence: 99%
“…Most widely studied methods for the oil extraction from plants involve either mechanical pressing (Subroto et al, 2015;Patil and Ali, 2006) or solvent extraction (Kostić et al, 2014); the last may be accomplished using solvent at both thermodynamic conditions: at room temperature and pressure or under subcritical (Liu et al, 2014;Ndlela et al, 2013) and supercritical (Jokić et al, 2010) conditions. Commonly, soybeans are solvent-extracted using commercial "hexane", a mixture of hydrocarbons with a boiling point around 65-69 • C that contains about 65% n-hexane and 35% of cyclopentane and hexane isomers (Kemper, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…[259,261] Hops, for example, are extracted to supply standardized hop aroma and oil seeds to obtain the triglycerides. [262][263][264] Also many other substances are produced on a smaller scale by extraction of plants using scCO 2 , as, for example, terpenes from orange oil, fatty oils and carotene-like pigments from sea buckthorn, corn oil from corn, wine aromas from wine or fragrances, and bioactive substances from various plants. [265][266][267] A well-known example for the extract being the value-added product is the use of scCO 2 to decaffeinate coffee.…”
Section: Cleaning and Extracting Agentmentioning
confidence: 99%